If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x^2-15x=13
We move all terms to the left:
-3x^2-15x-(13)=0
a = -3; b = -15; c = -13;
Δ = b2-4ac
Δ = -152-4·(-3)·(-13)
Δ = 69
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-15)-\sqrt{69}}{2*-3}=\frac{15-\sqrt{69}}{-6} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-15)+\sqrt{69}}{2*-3}=\frac{15+\sqrt{69}}{-6} $
| 32*x+2=34 | | 21*4.2=x | | -3x2+15x=7 | | -3x-15x=7 | | 65/50=x+36/x | | 4=d+2/3 | | 5/2x+1/6=2/3x+2 | | 3/4(12m+8)=2/3(6m+9) | | 3x2+15x=-13 | | 5(2x-1)^4=0 | | -5/3=-1/5x-7/4 | | -7w+15=2(w-6) | | 2 = h+5/3 | | y=-6(-2.3)-4 | | 4p-20=-26+3p | | 1/3x+1=1/6(2x+3) | | 8=d+5/4 | | -3x+4+5x=4x-12 | | 6p-22=2+2p | | 5x^2=-19x-12 | | 11=x/3+5 | | F(x+1)=4x^2+2x-3 | | 3x2-15x=-7 | | 14-x=17-5x | | 26=8+.25x | | 3x2-15=-7 | | k-3÷=10 | | 26=8+3/4x | | -12u=-24 | | k-3÷4=10 | | 2x+46=6x+6 | | -29=-v/5 |